Integrated sustainable management system: Drivers, strategy, structure, and evaluation - Irvan Khairil Solin; Luh Putu Mahyuni; Agus Fredy Maradona; Gede Sri Darma (Center for Science and Technology, IAIN Surakarta, 2023)
An integrated sustainable management system is the harmonization of multiple management systems into one system for addressing economic, social, and environmental challenges in a systematic and comprehensive manner, resulting in a more sustainable future for both the organization and interested parties. This system is driven by meeting the needs and expectations of interested parties based on the availability of resources by considering the sector and size of the business. System implementation can be carried out gradually, with full integration targets beginning at the organizational strategic level. Quality, environmental, and occupational health and safety are the three management systems harmonized by this system, and their control needs to be institutionalized in the hierarchical structure of the organization. The maturity level must be used to monitor and evaluate system performance regularly. Increasing the level of system maturity will have an impact on improving the achievement of organizational sustainability goals.